Testing for constituents: A response from Functional Discourse Grammar - Mackenzie, J. Lachlan (Language Under Discussion, 2019)
Timothy Osborne has surveyed a very large number of published introductions to grammatical analysis, all of which share the assumption that syntactic argumentation is to be conducted without reference to the meanings, uses and contexts of the example sentences. The purpose of Osborne’s article is to examine how well syntactic tests identify subphrasal strings as constituents. The aim of this discussion note is not to engage directly with this issue but to consider, from the viewpoint of Functional Discourse Grammar (FDG), the validity of the autonomous syntax assumption shared by Osborne and the authors whose work he considers. The note dwells on the hidden presence of functional and interactive notions in a methodology based on syntactic ‘tests’ and it is suggested that the difficulties encountered by that methodology (notably with regard to coordination) can be resolved insightfully by FDG with its four levels of analysis.